The Values of Islamic Education in the Hikayat Si Miskin: A Study of the Integration of Religion, Culture, and Contemporary Education - Fathin, Syarifah; Pranata, Jhon Petet; Faridah, Syarifah (Universitas Islam Negeri Raden Fatah Palembang, 2026)
This study examines the core Islamic educational values embedded within Hikayat Si Miskin, a canonical Malay literary work rich in moral, religious, and cultural symbolism, while analyzing its contemporary relevance to the integration of religion, culture, and pedagogy. Employing a qualitative descriptive approach through content analysis and a comprehensive literature review on scientific integration, the research identifies three pivotal dimensions of Islamic educational values: theological values (aqidah) manifested through tawakal, prayer, and gratitude; ethical values (akhlaq) evidenced by patience, sincerity, and self-improvement; and social values characterized by altruism, justice, and communal solidarity. These findings reveal a sophisticated synthesis of Islamic doctrine and Malay local wisdom, reflecting a life philosophy rooted in faith and morality. In the context of modern education, these values provide a robust framework for strengthening faith-based character development, designing culture-centric curricula, and establishing a holistic, contextual Islamic educational paradigm. Consequently, Hikayat Si Miskin transcends its literary status to serve as a vital instrument for reinforcing character and fostering the integration of religious and cultural identities within the contemporary educational landscape.